Analysis of Thought and Nusantara Islamic Movement - Moh Fayyad As; Zainuddin Syarif (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to describe the analysis of the thought and movement of Islam Nusantara within the socio-cultural context of Indonesia. Islam Nusantara, as a distinctive pattern of Islamic expression that has developed through the process of acculturation between Islamic teachings and local traditions, offers a model of religious practice that is moderate, tolerant, and contextual. This research employs a descriptive qualitative method based on library research through the examination of books, journal articles, and relevant previous studies. The findings indicate that the intellectual foundation of Islam Nusantara is rooted in cultural approaches, the practice of madhhab, moderation (wasathiyah), tolerance, and contextualization of Islamic teachings. In terms of movement, Islam Nusantara is manifested through socio-cultural activities, educational transformation through the role of pesantren, and national political movements that position nationalism as an inseparable part of faith. Islam Nusantara faces challenges from the rise of transnational ideologies, radicalism, and polarization within Islamic discourse. This study provides theoretical and practical contributions to the strengthening of literature on moderate Islam and serves as a reference for developing peaceful and harmonious religious life in Indonesia.